Indigenous Knowledge in Mundum and Suptulung - Rai, Shanti Devi (AMC Journal, 2021)
The dominance of formal education over the indigenous education along with the language and culture has been a pressing issue in almost all cultures of the world.  The Nepalese education system is also largely influenced by the western education system. So, it is inevitable that Nepalese students too are influenced by the western education. Rai community is one of 125 indigenous groups having rich indigenous knowledge. Particularly, they have vocational education of the food security that transforms the knowledge through the cultural practices, which is close to nature and thus a unique one. The significance of the food security means survival for the whole year. Mundumic education focuses on the survival in nature and to reduction of   poverty.  However, such indigenous type of cultural activities as part of education have not been recognized and put into priority in the government’s curriculum. This is an example of a missing link of such cultural heritage in our curriculum. Therefore, I propose here to explain a typical Binayo Movie thematically having indignity in its content suitable for inclusion in national curriculum. This Movie is a key to establish the Mundum and Suptulung identity within this community contributing to indigenous identity for the future generations. Thus, this article explores some significant aspects of Mundumic cultural education which helps conserve indigenous knowledge on the one hand, and on the other, reduce poverty through indigenous skills of food production and security.